2021
DOI: 10.1016/j.heliyon.2021.e07341
|View full text |Cite
|
Sign up to set email alerts
|

Leverage structure decisions in Bangladesh: managers and investors’ view

Abstract: The paper investigates the impact of managers' and investors' perceptions on financial leverage decisions in Bangladesh. To fulfill the purpose of the paper, the final structure of the questionnaire was made by adopting pretesting and assessment of outer factor loadings and measures the internal consistency of all items in the test or scale using Cranach's Alpha. The composite reliability (CR) was tested by calculating the composite alpha and average variance extracted (AVE). The study employs partial least sq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 69 publications
2
9
0
4
Order By: Relevance
“…Second, despite the possession of large fixed assets, firms tend to have limited access to the debt market; whereas, firms with less fixed assets enjoy a greater access to debt due to their familial and political affiliation. This result is supported by earlier evidences (Uddin, 2021;Ahmed et al, 2010). The results also indicated that large firms tend to have a fewer debt owing to their dependence on retained earnings.…”
Section: Conclusion and Policy Implicationsupporting
confidence: 85%
See 2 more Smart Citations
“…Second, despite the possession of large fixed assets, firms tend to have limited access to the debt market; whereas, firms with less fixed assets enjoy a greater access to debt due to their familial and political affiliation. This result is supported by earlier evidences (Uddin, 2021;Ahmed et al, 2010). The results also indicated that large firms tend to have a fewer debt owing to their dependence on retained earnings.…”
Section: Conclusion and Policy Implicationsupporting
confidence: 85%
“…(iv) The nature of ownership of Bangladeshi firms differs from those of developed countries to some extents; as an instance, firms in Bangladesh are considered for approval based on their political affiliation rather than their professionalism. Hence, the basis of financial decisions may not agree with the research findings from developed countries (Uddin, 2021). Furthermore, to the best of our knowledge, reasons why firms failed to consider all factors for capital structure decision in Bangladesh were not investigated in the previous studies.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Hutang sebagai peluang sekaligus ancaman yang harus diwaspadai, bauran pembiayaan perusahaan antara utang dan ekuitas haruslah optimal (Coulon, 2019; Uddin, 2021). Rasio hutang dapat diukur dengan membandingkan proporsi relatif hutang dengan ekuitas (Zutter & Smart, 2019), atau lebih dikenal dengan debt to equity rasio atau leverage rasio.…”
Section: Tinjauan Pustakaunclassified
“…Such policies are frequently chosen based on the views of shareholders, directors and management. Managers often select a leveraging structure that enables achievement of their firms aim (Uddin, 2021). This leverage structure provides a framework of the weighted average costs of the fund and firm value.…”
Section: Introductionmentioning
confidence: 99%